Market segmentation analysis : understanding it, doing it, and making it useful (2018)
‘Another book on market segmentation’ you think. Many outstanding marketing scientists, scholars and consultants have written excellent books on market segmentation. Some books offer practical advice to managers on how to best implement market segmentation in an organisation to ensure that the segmentation strategy is a success. Other books present sophisticated algorithms to extract market segments from consumer data. Our excuse for writing yet another book on market segmentation is to bridge the gap between the managerial and the statistical aspects of market segmentation analysis. We also want to give readers the opportunity to replicate every single calculation and visualisation we discuss in the book. We achieve this by making data sets used in the book available online (http://www. MarketSegmentationAnalysis.org) and by accompanying each section with R code. R is an open source environment for statistical computing and graphics, which is freely available for Linux, MacOS and Windows. Most of the examples used in the book relate to tourism. We have chosen tourism because most people go on vacation and, as a consequence, can relate to the examples, even if professionally they market an entirely different product. Tourism is also very complex compared to other products: a trip consists of many different elements, typically a number of decision makers are involved in the planning process, travel can be motivated by a wide range of motives, and manifests in tourists engaging in an even wider range of activities. Tourists can plan their trip of a lifetime for decades or ‘impulse purchase’ a city trip a few hours before departure. As a consequence of the complexity of tourism as a product, many alternative market segmentation approaches can be used to break the market down into smaller, more homogeneous consumer groups or market segments. In the case of marketing toothpaste, for example, consumers can be segmented by their willingness to pay or by benefits sought. Tourists can, in addition, be grouped based on their preferences for vacation activities, the people they travel with, how long they travel, whether or not they stay at the same destination or visit a number of destinations, the degree to which they perceive risks to be associated with their trip, their expenditure patterns, their level of variety seeking and so on.